Control of Ultra-deep Strike-slip Fault Reservoir and Hydrocarbon Migration: A Case Study of HD Block in Tarim Basin - Wang, Huailong; Dan, Guangjian; Zhang, Jie; Li, Xiangwen; Lu, Zhongyuan; Liu, Yonglei; Zhang, Lei; Xu, Jianyang (European Journal of Applied Sciences, 2023)
The reservoirs in the HD area, Tarim Basin, are strictly controlled by the distribution of faults. On the basis of the latest high-precision three-dimensional seismic data as well as an understanding of the strike-slip fault theoretical model, the structural styles, assembly of major and secondary faults, movement history and relationship between fault activity and hydrocarbon accumulation are determined in the forms of seismic related section illustration and planar appearance. The study shows that the NE-oriented strike-slip faults of the Ordovician was activated from the middle Caledonian period and that the northern part displayed stronger activity than the southern part. This fault belt is the major fault in the study area and serves as the first-order oil source fault. The south-north thrust fault started to move in the early Hercynian and intersected with the main strike-slip faults. Considering the distribution of thrust, this fault acts as the secondary oil source fault. The hydrocarbons in the Ordovician reservoir are predominantly transferred by vertical in situ migration through SSFs and thrust faults. These faults cut deep into the source layer and played a major role in hydrocarbon migration. The NW-trending secondary SSF in the central part of the study area was formed in the middle and late Caledonian. The fault mainly controls the distribution of the reservoir and contributes little to hydrocarbon transfer. Therefore, the hydrocarbon potential around this fault is unfavorable.